Design of an innovative industrial system driven by renewable energy for achieving thermal energy storage, carbon capture and clean fuels - Akgun, Ibrahim; Dincer, Ibrahim (ELSEVIER, 2025)
This investigation presents an innovative and resilient multigeneration system designed to mitigate carbon dioxide emissions in cement manufacturing plants and facilitate the clean production of hydrogen and methanol. The system utilizes the calcium looping cycle (CLC) to capture carbon dioxide from cement production processes, subsequently converting it into methanol. In this regard, the system employs solar energy to heat molten salt, which is stored in a thermal energy storage tank and provides energy to both Rankine and organic Rankine cycles for power generation. During periods of low solar radiation, the stored molten salt is employed to support the methanol synthesis process, in improving the system efficiency and hence sustainability. Alkaline electrolysis, powered by wind energy, generates the hydrogen used in the system. Some of the produced hydrogen reacts with carbon dioxide to form methanol, while the remainder is stored in a hydrogen tank. The system generates 5528 kW of power output and 802.65 kg/h of hot water as valuable by-products. Additionally, the system achieves a hydrogen production rate of approximately 7.42 kg/h and a methanol production rate of approximately 146.95 kg/h. Moreover, the system demonstrates an energetic efficiency of 71.26 % and an exergetic efficiency of 60.42 %. The analysis study further demonstrates that the captured CO2 rate and the produced H2 rate are critical parameters for the system. As the captured CO2 rate increases from 0.01 kg/s to 0.1 kg/s, there is an enhancement in overall energy efficiency from 70.22 % to 72.25 % and in overall exergy efficiency from 59.38 % to 61.41 %. Similarly, as the H2 production rate increases from 0.01 kg/s to 0.1 kg/s, energy efficiency rises from 71.28 % to 76.62 %, while exergy efficiency increases from 60.43 % to 63.21 %.
Keywords: Cement; Methanol; Hydrogen; Exergy; Energy; Efficiency; Carbon capture; Thermal energy storage; Renewable energy; TECHNOLOGIES; DIOXIDE; WASTE; CYCLE; Energy & Fuels